Veracity and rhetoric in paediatric medicine: a critique of Svoboda and Van Howe's response to the AAP policy on infant male circumcision. Issue 7 (16th August 2013) - Morris, Brian J; Tobian, Aaron A R; Hankins, Catherine A; Klausner, Jeffrey D; Banerjee, Joya; Bailis, Stefan A; Moses, Stephen; Wiswell, Thomas E
Abstract : In a recent issue of the Journal of Medical Ethics, Svoboda and Van Howe commented on the 2012 change in the American Academy of Pediatrics (AAP) policy on newborn male circumcision, in which the AAP stated that benefits of the procedure outweigh the risks. Svoboda and Van Howe disagree with the AAP conclusions. We show here that their arguments against male circumcision are based on a poor understanding of epidemiology, erroneous interpretation of the evidence, selective citation of the literature, statistical manipulation of data, and circular reasoning. In reality, the scientific evidence indicates that male circumcision, especially when performed in the newborn period, is an ethically and medically sound low-risk preventive health procedure conferring a lifetime of benefits to health and well-being. Policies in support of parent-approved elective newborn circumcision should be embraced by the medical, scientific and wider communities.